Teachers’ Knowledge and Attitudes Towards Trauma-Informed Practices - Septinda Rima Dewanti; Eko Pramudya Laksana; Septinda Rima Dewanti; Eko Pramudya Laksana (Universitas Negeri Malang, 2025)
The impact of complex childhood trauma can interfere with students' personal and academic development. Although many studies suggest the vital role of educators in supporting trauma-impacted students, research on this topic is minimal. This study investigates teachers’ knowledge and attitudes towards trauma-informed practices in school. Data was collected from the 32-hour workshop on trauma-informed practices, and a quantitative analysis was conducted to compare teachers’ knowledge of trauma-informed practices before and after the workshop. Then, teachers’ attitudes toward implementing this approach were analysed. A Wilcoxon test result shows significant differences in teachers’ knowledge before and after the workshop (p<0.001). Findings also indicate a positive attitude towards trauma-informed practices in school, where most participants (n=66, 85%) indicated that they want to implement trauma-informed practices in school. Therefore, occupying teachers with trauma-informed practice skills can be potentially helpful in supporting students who show challenging behaviours due to disruption caused by adverse childhood experiences.